The Suffering of Palestinian Children in Qishash Athfal Najaw Min Bayni Fakkay Al-Mawt Fi Ghazah by Yusra Al-Aklouk: Literary Sociology of Ian Watt - Bima sakti; Abdul Basid (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines the various forms of suffering experienced by Palestinian children as portrayed in Qishash Athfal Najaw min Bayni Fakkay al-Mawt fi Ghazah. This approach explores the close relationship between the socio-political conditions of Gaza, the humanitarian impact of the ongoing conflict, and the trauma and violence reflected in children's narratives. Using a descriptive qualitative analysis, the study interprets data contextually through close reading without manipulating variables, emphasizing the understanding of textual phenomena and narrative elements. The research applies Ian Watt’s sociology of literature in combination with the interactive analysis model of Miles and Huberman to examine eighteen story fragments selected through purposive sampling. The findings reveal that Al-Aklouk’s narrative depicts children’s suffering through wounded bodies, profound trauma, forced maturity, and the persistent threat of war. Ultimately, the text serves as a moral witness to global injustice and affirms literature’s role as a medium of resistance and humanitarian advocacy.